THE EFFECTIVENESS OF USING PUZZLES IN IMPROVING STUDENTS' MOTIVATION IN LEARNING ENGLISH - Maya Rosmayanti, - (2008)
This study entitles "The Effectiveness of Using Puzzles in Improving Students' Motivation in Leaming English (An Experimental Study in the Eleventh Grade Students of SMK N 4 Bandung)". This study investigates whether puzzle is effective in improving students' motivation in learning English and identifies the advantages and disadvantages of using puzzles in English classroom. The study was carried out at the eleventh grade students of SMK N 4 Bandung. Having used the random sampling, these students were assigned to an experimental group and a control group. The experimental group was given several treatments in the period of four meetings, while the control group was not given any treatment. Pretest-postest design which is the subset of quasi experimental design was used to conduct the research. Data collection was conducted by doing questionnaire before the treatment, questionnaire after the treatment, puzzle questionnaire and interviews. The t-test procedures were used in analyzing the data from questionnaire before the treatment and questionnaie after the treatment. Furthermore, the data from puzzle questionnaire and interview, which was only administered to the experimental group, were analyzed to examine the advantages and the disadvantages of using puzzles. The result of data analysis showed that there were significant difference between the questionnaire before the treatment and questionnaie after the treatment result of two groups, or in other words both groups have a different level of motivation in learning English. In addition, the data result from puzzle questionnaire and interviews showed that puzzles have advantages and disadvantages both for students in their motivation in learning English and for teacher in her teaching. In conclusion, using puzzle in English classroom is effective in improving students' motivation in learning English.